2020
DOI: 10.3390/su12229765
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Cross-National Differences in Automated Vehicle Acceptance

Abstract: The technology that allows fully automated driving already exists and it may gradually enter the market over the forthcoming decades. Technology assimilation and automated vehicle acceptance in different countries is of high interest to many scholars, manufacturers, and policymakers worldwide. We model the mode choice between automated vehicles and conventional cars using a mixed multinomial logit heteroskedastic error component type model. Specifically, we capture preference heterogeneity assuming a continuou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 49 publications
6
23
0
Order By: Relevance
“…Findings demonstrate a substantial difference in acceptance across countries, while people show large reservations about the use of AVs. Our paper advances the study of Etzioni et al [65], focusing on gender-based travel preferences using AVs across seven different countries and discuss potential cultural influences on AV vs SAV usage and the impact of cotravellers' gender on ride sharing acceptance.…”
Section: Literature Reviewmentioning
confidence: 74%
See 3 more Smart Citations
“…Findings demonstrate a substantial difference in acceptance across countries, while people show large reservations about the use of AVs. Our paper advances the study of Etzioni et al [65], focusing on gender-based travel preferences using AVs across seven different countries and discuss potential cultural influences on AV vs SAV usage and the impact of cotravellers' gender on ride sharing acceptance.…”
Section: Literature Reviewmentioning
confidence: 74%
“…Three travel alternatives options were offered to each respondent. This article extends the analysis of Etzioni et al [65], which focused on choices between a conventional car and an AV, by focusing on the willingness to share either a vehicle or a ride versus a PAV. The three-step method design is outlined here:…”
Section: Methodsmentioning
confidence: 80%
See 2 more Smart Citations
“…Travelers plan their daily travel in a way to maximize their benefits. It is found that travelers are willing to pay money to reduce the time spent on traveling, thus maximizing their utility [9,29]. In the time allocation theory, travel time is considered as a consumption, which means an expense rather than the gaining of money, just like in the case of activity time [23].…”
Section: Literature Reviewmentioning
confidence: 99%